Estudo da sorção de tensoativos orgânicos em argilas bentoníticas. - Silva, Darciely Lindalva da (2013)
Currently there are increasing studies on bentonite clays are organically modified. Since the method involves the addition of surfactants (sufactantes) ionic or nonionic most studied in the synthesis of organoclays, so that the synthesis can be performed in two ways: by ion exchange (the chemical reaction of double exchange) and ion -dipole (organic molecules are adsorbed on the surface of clay). Thus, the present work aims to study the sorption / cation exchange of ionic and nonionic surfactants on the surface of bentonite clays making them organophilic. In the process of organophilization bentonite clays have used two industrialized Brasgel PA and the Bentongel that their concentrations were varied from 3.16 to 7.16% by weight of clay. Was used to organophilization one nonionic surfactant amine ethoxylate grade 5 TA 50, where its concentration pierced 40-60 g/100g. After organophilizated clays were filtered, dried in an oven for 48 hours and passed in ABNT No. 200, to be well characterized. The sorption isotherms were constructed using data from thermogravimetry (TG), and adjusted to the linear model and Freundlich. From the isotherms was possible to infer the mechanism involved in the sorption is adsorption and cooperative multilayer adsorption, and the type of clay, the type of surfactant and the viscosity of the medium, variables influenced sorption. According to the results, it was possible to infer that clays with higher sorption capacity were Bentongel and Brasgel concentration of 3.16% when the WB organophilizated the Bentogel concentration of 7.16% organophilizated when the MT 50 and the Brasgel concentration 3.16% when organophilizated with TA 50.